Comparative analysis of newly graduated nurse support through periods of turmoil: lessons learnt for building a future workforce for uncertain times - Casey Riches; Rachael Pitt; Scott Tyler; Megan Wise; Philip Watman; Amanda Henderson (BMC, 2024)
Abstract Aim To compare newly graduated nurse retention and employment experiences across two distinct graduate nurse programs through periods of health care delivery stability and instability. Background A global nursing workforce shortage, coupled with increasing demands on health services, requires a specific focus on building capability and improved retention of nurses. The graduate nurse cohort is a critical supply source that potentially can be harnessed if their needs are better understood. Design A longitudinal (2015-2023) cross-sectional design was used to examine retention and experiences of newly graduated nurses from two ('traditional, unit-based' versus 'mobile') supported programs. Methods Retention rates were obtained through analysis of employment databases. Descriptive data on impressions and experiences was collected at two time points via a short series of questions contained in a survey, from graduate nurses who remained in employment. Results Retention rates for graduate nurses were high (85%) during periods of stability, but even higher for the 'mobile' graduate nurse program. Both programs were adversely affected by instability however, the impact was substantial (around 50%) for the peak period of instability (2020) in the 'mobile' program. Survey data indicated that during the period of instability graduate nurses in traditional, unit-based programs had a more positive experience when compared with graduate nurses participating in the 'mobile' program; This contrasts with the period of stability, where graduate nurses in the 'mobile' program indicated more positive responses. Discussion Findings re-emphasise the importance of supportive structures for newly graduated nurses as effective in retaining these staff. However, for the first time, evidence is provided that 'mobility', diversity, and difference can be viewed positively by graduate nurses. Furthermore, it provides improved understanding about mechanisms, support and boundaries, all interrelating factors, in 'stretching' capacity of graduate nurses. Conclusion Longitudinal analysis of graduate nurses, participating in two diverse programs, through periods of stability and instability offers insights into their challenges and outcomes. These insights can directly inform targeted strategies for inclusion in supported programs that lead to improved graduate nurse retention and contribute to building an agile nursing workforce.